2022
DOI: 10.1093/braincomms/fcac225
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala subnuclear volumes in temporal lobe epilepsy with hippocampal sclerosis and in non-lesional patients

Abstract: Together with hippocampus, the amygdala is important in the epileptogenic network of patients with temporal lobe epilepsy. Recently, an increase in amygdala volumes (i.e., amygdala enlargement) has been proposed as morphological biomarker of a subtype of temporal lobe epilepsy patients without MRI abnormalities, although other data suggest that this finding might be unspecific and not exclusive to temporal lobe epilepsy. In these studies, the amygdala is treated as a single entity, while instead it is composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…Of note, considering the presence of hippocampal sclerosis, only one ICA‐TLE patient presented with this radiological finding, while this was evident in five noICA‐TLE patients. As already reported in the literature, it was demonstrated that HS was significantly associated with volumetric reduction of the ipsilateral amygdala and, in particular, of the BLA 27 . It could be argued that amygdalar atrophy could partially explain the volumetric differences between these two groups.…”
Section: Discussionsupporting
confidence: 68%
“…Of note, considering the presence of hippocampal sclerosis, only one ICA‐TLE patient presented with this radiological finding, while this was evident in five noICA‐TLE patients. As already reported in the literature, it was demonstrated that HS was significantly associated with volumetric reduction of the ipsilateral amygdala and, in particular, of the BLA 27 . It could be argued that amygdalar atrophy could partially explain the volumetric differences between these two groups.…”
Section: Discussionsupporting
confidence: 68%
“…Recently in Brain Communications , Ballerini et al . 2 add further evidence to the above by ‘dismantling’ the amygdala. Previous studies 3 , 4 already demonstrated trophic changes of the amygdala as a whole, in patients with temporal lobe epilepsy (TLE).…”
mentioning
confidence: 60%
“…The current study by Ballerini and colleagues 2 has limitations. While the subregional amygdala segmentation is clearly an advance, its validity in people with epilepsy still needs to be established.…”
mentioning
confidence: 78%
See 2 more Smart Citations